KOMPETENSI PROFESIONAL GURU IPS TERPADU (SEJARAH) DI SMP NEGERI I LEMBAH GUMANTI - Sari, Ita Yumanda; Zafri, Zafri; Nazmi, Ranti (Pendidikan Sejarah, 2014)
This study pupouse to describe the competence of professional teacher social sciences (history) in Junior High School 1 Lembah Gumanti. There are twelve teacher professional competences according to Hamalik O. Emar. In this case the author do observation to the classroom in teacher explain the lesson. After that the author do interview. This research/study was done in three meetings. The object of research/study is the social sciences (history) teachers, the students and the headmaster of Junior High School 1 Lembah Gumanti. The data collected is related to observation study and the interview. The technique of data collecting by collected data, reduction data, display data and make the conclusion. Taken from the observation sheet by using a checklist list. According to the result of the research that the social science teacher of Junior High School I Lembah Gumanti are Professional teacher because they are can do the twelve Professional competence said Hamalik O. Emar. The research showed that by doing the twelve teacher Profesional competence in learning of social Sciences (history) can increase the competence of Profesional teacher.